N-terminal pro-brain natriuretic peptide in systemic sclerosis: a new cornerstone of cardiovascular assessment?. Issue 12 (3rd December 2008) - Allanore, Y; Wahbi, K; Borderie, D; Weber, S; Kahan, A; Meune, C
Abstract : Background: Cardiac involvement, a common and often fatal complication of systemic sclerosis (SSc), is currently detected by standard echocardiography enhanced by tissue Doppler echocardiography (TDE). Objective: The performance of the biomarker of cardiovascular disease, N-terminal pro-brain natriuretic peptide (NT-proBNP), in the detection of cardiac involvement by SSc was examined. Methods: A total of 69 consecutive patients with SSc (mean (SD) age 56 (13) years, 56 women) were prospectively studied with standard echocardiography and TDE measurements of longitudinal mitral and tricuspid annular velocities. Plasma NT-proBNP was measured in all patients. Results: Overall, 18 patients had manifestations of cardiac involvement, of whom 7 had depressed left ventricular and 8 depressed right ventricular myocardial contractility, and 8 had elevated systolic pulmonary arterial pressure. Patients with reduced contractility had increased mean (SD) NT-proBNP (704 (878) pg/ml versus 118 (112) pg/ml in patients with normal myocardial contractility, p<0.001). Similarly, NT-proBNP was higher in patients with (607 (758) pg/ml) than in patients without (96 (78) pg/ml) manifestations of overall cardiac involvement (p<0.001). Receiver operating characteristic analysis showed NT-proBNP reliably detected depressed myocardial contractility and overall cardiac involvement (area under the curve 0.905 (95% CI 0.814 to 0.996) and 0.935 (95% CI 0.871 to 0.996), respectively). Considering patients with SSc with normal echocardiography and TDE as controls, and using a 125 pg/ml cut-off concentration, sensitivity and specificity were 92% and 71% in the detection of depressed myocardial contractility, and 94% and 78% for overall cardiac involvement. Conclusions: NT-proBNP reliably detected the presence of cardiac involvement and appears to be a very useful marker to risk stratify patients presenting with SSc.